2006
DOI: 10.1089/neu.2006.23.976
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Fibrinolysis and Traumatic Brain Injury in Mice

Abstract: Traumatic brain injury (TBI) has been associated with intravascular coagulation, which may be a result of thromboplastin released following brain injury. Clots thus formed are lysed by plasmin, which is activated by tissue-type and urokinase-type plasminogen activators (uPA). To evaluate the association between traumatic intravascular coagulation and post-traumatic outcome, uPA knockout (uPA-/-) transgenic mice (n=12) or wild-type littermates (WT; n=12) were anesthetized and subjected to controlled cortical im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
2
9
2
Order By: Relevance
“…In the present study, however, the lesion volume, ratio of ipsilateral to contralateral cortical volumes, and the rostrocaudal extent of the cortical lesion at 6 or 8 months post-CCI were similar between genotypes. Thus, our findings did not confirm previous observations of a neuroprotective effect of uPA in a kainate-induced SE model [42] or CCI TBI model [26]. The differences in the findings could relate to the type of injury induction (SE vs. TBI).…”
Section: Upa Deficiency Did Not Affect the Severity Of Post-cci Corticontrasting
confidence: 99%
See 2 more Smart Citations
“…In the present study, however, the lesion volume, ratio of ipsilateral to contralateral cortical volumes, and the rostrocaudal extent of the cortical lesion at 6 or 8 months post-CCI were similar between genotypes. Thus, our findings did not confirm previous observations of a neuroprotective effect of uPA in a kainate-induced SE model [42] or CCI TBI model [26]. The differences in the findings could relate to the type of injury induction (SE vs. TBI).…”
Section: Upa Deficiency Did Not Affect the Severity Of Post-cci Corticontrasting
confidence: 99%
“…Also, the timing of the analysis was different as Morales et al [26] analyzed the data at 2 weeks post-CCI, whereas, our analysis was performed 6 to 8 months post-CCI. Also, while C57BL/6J mice from Jackson Laboratories® were used in both the present and the previous study [26], it is likely that the genetic background of the animals was not identical as they were bought from different vendors at different times, which could affect the findings [44]. Interestingly, Nagai et al [45] reported no difference in infarct size between Plau-deficient and Wt mice at 24 h after focal cerebral ischemia.…”
Section: Upa Deficiency Did Not Affect the Severity Of Post-cci Cortimentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, these data indicate that the expression of uPA and uPAR increase in the sub-acute, recovery stages of ischemic stroke, and suggest that uPA binding to uPAR plays a central role in the process of neurorepair following an acute ischemic injury. These observations are supported by reports from other groups indicating that uPAR modulates peripheral nerve regeneration after a crush nerve [21] , and that genetic deficiency of uPA aggravates the motor deficit and increases neuronal death in an animal model of traumatic brain injury [26] .…”
Section: Upa and Upar In The Ischemic Brainsupporting
confidence: 84%
“…[17][18][19] The major limitation in patient studies relates to the lack of histological verification of imaging findings. Even though several clinically relevant animal models of TBI are available, 20 studies applying functional imaging after experimental TBI are scarce. A few studies have focused on…”
Section: Introductionmentioning
confidence: 99%